2017
DOI: 10.1097/bpb.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

Surgical resection of osteoid osteoma and osteoblastoma of the spine

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 31 publications
1
20
0
2
Order By: Relevance
“…Literature shows that the rate of recurrence of OO is higher after intralesional resection compared with en bloc resection. [ 3 , 5 ] We did not have any recurrence in our series. No patient deteriorated neurologically after surgical excision.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Literature shows that the rate of recurrence of OO is higher after intralesional resection compared with en bloc resection. [ 3 , 5 ] We did not have any recurrence in our series. No patient deteriorated neurologically after surgical excision.…”
Section: Discussionmentioning
confidence: 59%
“…Surgical intralesional excision has been the commonly accepted treatment for a long time. [ 3 , 5 ] The goal of OO surgery is to remove the nidus entirely without causing pathologic fracture, especially of the facets and pedicles or disrupting the adjacent uninvolved tissues. The posterior approach was carried out in all the surgical patients.…”
Section: Discussionmentioning
confidence: 99%
“…Rajasekaran et al reported a slightly higher mean operative time of 74 minutes and a similar length of the incision (3-4 cm), with a complete resection in all cases [12]. Kadhim et al performed a resection under O-arm or C-arm both associated with the navigation [13]. They reported a mean operative time of 123 minutes and a complete resection confirmed intraoperatively by a reacquisition in each case.…”
Section: Discussionmentioning
confidence: 99%
“…Intraoperative localization and identification of the nidus guided by CT or 99mTc have been reported (6). Additionally, intraoperative radiographic guidance through 2-D navigation with the C-arm and recently with 3-D navigation with the Oarm has been also described (71,72).…”
Section: Treatmentmentioning
confidence: 99%